2018
DOI: 10.1021/acs.cgd.8b00960
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Catalytic Properties in a Family of Ag(I)-Benzotriazole Based Coordination Compounds

Abstract: In this work we study the coordination chemistry of a series of semi-rigid benzotriazole based ligands (L 1-L 3) along with the low coordination number but versatile Ag I ions. This has led to nine new coordination compounds formulated [Ag(L 1)(CF3CO2)] (1), [Ag2(L 1T)2(CF3SO3)2]•2Me2CO (2), [Ag(L 2T)(ClO4)(Me2CO)] (3), [Ag(L 2T)(BF4)(Et2O)] (4), [Ag2(L 3T)2(ClO4)2]2 (5), [Ag(L 3)(NO3)] (6), [Ag2(L 3T)2(CF3CO2)2] (7), [Ag2(L 3T)(CF3SO3)2] (8) and [Ag2(L 3T)2(CF3CF2CO2)2]•2Me2CO (9). These compounds show struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 109 publications
(225 reference statements)
0
16
0
Order By: Relevance
“…Multiple strategies have been implemented in the literature. Previous studies in A 3 coupling reactions have shown that coinage metals are powerful catalysts for A 3 coupling reactions . Despite great achievements in the past two decades in the field of A 3 coupling, these reactions still suffer from some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple strategies have been implemented in the literature. Previous studies in A 3 coupling reactions have shown that coinage metals are powerful catalysts for A 3 coupling reactions . Despite great achievements in the past two decades in the field of A 3 coupling, these reactions still suffer from some shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…We have also attempted to elucidate the reaction mechanism from an inorganic perspective; through a thorough synthesis and study of targeted coordination compounds, we evaluated how factors such as coordination geometry, anion, and ligand tuning affect the catalytic activity. One year later, inspired by the successful Ag-based paradigms described above, we elucidated the efficacy of Ag-benzotriazole compounds in promoting the A 3 coupling [120]. From our studies, we identified compound [Ag(L)(BF4)(Et2O)] (8) as the optimum One year later, inspired by the successful Ag-based paradigms described above, we elucidated the efficacy of Ag-benzotriazole compounds in promoting the A 3 coupling [120].…”
Section: Scheme 57 (Left)mentioning
confidence: 84%
“…Good to excellent yields (67 -95%) of the relevant substrates were generated under the optimal conditions and using only 1 mol% of the catalytic precursor. The next compound in this family of catalysts was generated from the reaction of pbta with the Ru II (p-cymene) chloride dimer, leading to the synthesis of [Ru II (pbta)(pcymene)Cl]•Cl (156) as reported in a following study [126]. In this case, the Ru II centre coordinates to pbta in a bidentate fashion through the N2 atom of the triazole moiety and the pyridine nitrogen (Figure 24, right).…”
Section: N1-substituted Benzotriazolesmentioning
confidence: 95%
“…Having created a library of CPs with catalytic activity using these benzotriazole-based linkers, the next step in our research efforts was to combine this ligand system with the rich chemistry, unique coordination capabilities and superior alkynophilicity of Ag I ions. These attempts are documented in a recent study which reports the synthesis of multiple new compounds using ligands bbpm, bbmm and bbom [156]. The complexes exhibit a large structural diversity of 0D dimers and 1D / 2D CPs with interesting topological features and architectures.…”
Section: N1-substituted Benzotriazolesmentioning
confidence: 99%